Inhibition of RAGE Attenuates Cigarette Smoke-Induced Lung Epithelial Cell Damage via RAGE-Mediated Nrf2/DAMP Signaling - Lee, Hanbyeol; Lee, Jooyeon; Hong, Seok-Ho; Rahman, Irfan; Yang, Se-Ran (Frontiers in Pharmacology, 2018)
The oxidative stress and cellular apoptosis by environmental factor including cigarette smoke induces alveolar airway remodeling leading to chronic obstructive pulmonary disease (COPD). Recently, the receptor for advanced glycan end products (RAGE) which is highly expressed in alveolar epithelium is emerging as a biomarker for COPD susceptibility or progression. However, it still remains unknown how RAGE plays a role in cigarette smoke extract (CSE)-exposed human alveolar type II epithelial cell line. Therefore, we determined the efficacy of RAGE-specific antagonist FPS-ZM1 in response to CSE-induced lung epithelial cells. CSE induced the elevated generation of RONS and release of pro-inflammatory cytokines, and impaired the cellular antioxidant defense system. Further, CSE induced the alteration of RAGE distribution via the activation of redox-sensitive DAMP (Damage-associated molecular patterns) signaling through Nrf2 in cells. Although pre-treatment with SB202190 (p38 inhibitor) or SP600125 (JNK inhibitor) failed to recover the alteration of RAGE distribution, treatment of FPS-ZM1 significantly exhibited anti-inflammatory and anti-oxidative/nitrosative effects, also inhibited the activation of redox-sensitive DAMP signaling through Nrf2 (nuclear factor erythroid 2-related factor 2) migration in the presence of CSE. Taken together, our data demonstrate that RAGE and Nrf2 play a pivotal role in maintenance of alveolar epithelial integrity.